Artigo Original Caetano JA, Pacliuca LMF. Cartilha sobre auto-exame ocular para portadores do HIV/AIDS como tecnologia emancipatória: relato de experiência. Rev. Eletr. Enf. [Internet]. 2006;8(2):241-9. Available from: http://www.fen.ufg.br/r - Joselany Áfio Caetano; Lorita Marlena Freitag Pagliuca (Universidade Federal de Goias, 2006)
This work describes the experience of the one construction an ocular self-examination primer to the HIV/SIDA porters' and had as objective to develop and to evaluate the actions of the self-examination for intermediary of ocular self-examination primer. The testing process was done by the educative groups and the bimonthly nursing consultancy, followed by the ophthalmologic examination. Leaning on the NIETSCHE (2000) ideas, we marked this material as an emancipated technology because it brings, to this population, the opportunity of if freeing of a subjection stage. The results prove that the HIV/SIDA porters' if feel motivated to investigate ocular problems, but it is still missing the primer usage habit incorporation in the quotidian life. More than to offer sequential steps to do the ocular self-examination technique, we presented points that help on the potentialities development from the HIV/SIDA porters aiming to improve the self-care with the eye in a dynamic way and accompanied by an allied, is the educative material.